From diverticulum to diagnosis: The distinctive role of Endoscopic Ultrasonography in Lemmel syndrome - Xin Chen; Xingkang He; Xiaoli Chen; Qian Cao (PLoS ONE, 2025)
Background and aim Lemmel syndrome is a rare cause of obstructive jaundice, induced by periampullary diverticulum(PAD). Endoscopic Ultrasonography(EUS) is helpful in detecting PAD and differentiating the obstruction cause in Lemmel syndrome by exposing the detail of ampulla structure and measuring the dilatation of common bile duct and pancreatic duct. Materials and methods Nineteen patients diagnosed Lemmel syndrome by EUS in our institute between January 1, 2019 to April 30, 2024 were enrolled. Their demographics, laboratory and imaging data were analyzed. Results The patients diagnosed with Lemmel syndrome were mostly elder male with the average age of 68.8 ± 2.4 years. We found Lemmel syndrome patients most present with a dilatation in middle and upper segments of common bile duct. Magnetic resonance cholangiopancreatography (MRCP), abdominal computed tomography (CT) and upper abdominal enhanced MR were all failed to diagnose Lemmel syndrome. Besides, a higher serum level of alkaline phosphatase was predominant in those complicating with cholecystitis or cholecystolithiasis than those without complications. Conclusions Similar with non-invasive imaging examination, EUS was capable of confirming the diagnosis of Lemmel syndrome, evaluating PAD and pancreaticobiliary duct as well as periampullary structure. EUS could be a useful investigate method to distinguish Lemmel syndrome for patients with unexplained dilated common bile duct or jaundice.